Risk Factors for Psychosis: Impaired Social and Role Functioning - Cornblatt, Barbara A. (Oxford University Press, 2012)
Objectives: Risk for psychosis is currently defined primarily on the basis of attenuated positive symptoms (APS), with no inclusion of the functional deficits characteristic of schizophrenia. Impaired social and role functioning have been of interest for reflecting poor outcome but far less is known about the developmental impact of these deficits as vulnerability or risk factors. Methods: Age-appropriate social and role functioning were prospectively assessed in 100 individuals at clinical high risk (CHR) for psychosis included in the 8-site North American Prodromal Longitudinal Study database. A nested case-control design was used to compare changes in social and role functioning in 26 individuals converting to psychosis shortly after baseline assessment and 24 converting over a year later. Individuals in each converter subgroup were directly matched to a non-converter at the same site, controlling for time to conversion, age, gender, and severity of baseline symptoms. Results: At baseline, CHR subjects who later became psychotic were significantly more likely to be impaired socially than matched non-converters. Onset of psychosis did not further disrupt social difficulties. Role functioning showed some of the same trends, but the overall pattern was not as consistent as for the social domain. Controlling for neurocognition did not change the pattern of group differences. Conclusions: Early impaired social functioning appears to be a risk factor for psychosis and, added to APS, could potentially contribute to accurate identification of CHR individuals and provide a new direction for early intervention to reduce long-term disability.